The democratic accountability of the European Central Bank - BINI-SMAGHI, L. (PSL Quarterly Review, 2013)
The European Central Bank (ECB) is considered to be an institution with a high level of accountability compared with other central banks. However, the matter has yet to be investigated in practice. Accountability of the ECB will have to be checked by governing bodies both within and outside the ECB as well as the public. A survey is undertaken of the main reasons for central bank accountability, especially for the ECB. JEL Codes: A01